In cylinder expansion of ring crevice and oil film hydrocarbons in SI engines - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
A computational approach has been presented for calculation of just-past-port hydrocarbons (HCs) released from ring crevices and oil film. Time dependent in cylinder gas concentrations are calculated based on the simplest combustion reaction assumption, i.e. complete theoretical combustion (lambda = 1), and a cosine law for the combustion rate. Until the time the HC release starts, the fresh charge, or its mixture with combustion products, is assumed to be distributed homogeneously in the combustion chamber so that the governing equations need not be solved for this period. After that, the governing equations have been introduced for solution of the flow field except that the energy equation is replaced with a simple zero-dimensional phenomenological submodel at the expense of solution of the N-S equations. Post flame oxidation is not taken into account. Results are compared to the extent limited counterparts in the literature allow, due to the lack of common parameters adopted in many of different studies. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: hydrocarbon emissions; ring crevice; oil film; spark ignition engine